The role of social identity theory and employer attractiveness in recruiting workers acrossgenerations for healthcare organisations: the case of a major private hospital - Archer, Catherine (University of Western Australia, 2008)
This paper uses the lens of Social Identity Theory (Ashforth & Mael 1989; Tajfel 1982), frompsychology and organisational psychology literature, and the concept of employer branding (Ambler& Barrow 1996; Ewing et al. 2002) from the marketing discipline, to investigate differing perceptionsof employer attractiveness across different generations of potential and current employees. Thispaper presents a case study of a major private hospital in Western Australia which aims tocontribute towards a better understanding of how managers can attract workers with increasinglydisparate expectations of their working life in a highly ?gendered? profession. To date no study haslooked at whether a strong employer brand has the same resonance for different individuals withinand outside an organisation and across different age groups and levels of experience. The currentstudy is important from an industry perspective for two main reasons. Firstly, the shortage of skilledworkers has become a prominent aspect of the Australian economy with calls in the business pressfor better marketing to prospective employees (Moses 2006). The healthcare industry, not only inAustralia but also in many other developed nations, has been particularly badly affected. Secondly,the aging population means that no generation of workers can be ignored in the fight for talent. Thedemand for trained nurses is increasing at the same time as the supply is declining (Creswell 2005).